Development and validation of a Teacher Belief Survey for the constructivist classroom - Von Oppell, Monika; Aldridge, Jill (Rowman & Littlefield, 2020)
The research reported in this article was part of a larger study which took place in Abu Dhabi, United Arab Emirates. The large-scale education reform, being carried out at the time of the study, required paradigm shifts in practice; from a traditional to a constructivist approach. The education reform posed on-going challenges and posed questions regarding the future impact for teachers, particularly with respect to their beliefs with respect to classroom practice. This article describes the development and validation of a survey to assess teachers’ beliefs in this new context. The survey assesses teachers’ beliefs about their role in the classroom and philosophy of teaching and learning and their classroom practice. The translation validity of the survey was supported by examining the content and face validity. Further, analysis of the data collected 182 Arab teachers was used to provide support for the reliability and validity of the newly developed Teacher Belief Survey in terms of factor structure, internal consistency reliability, discriminant and concurrent validity. This instrument has the potential to be useful for ascertaining teachers’ professional development needs and for understanding the beliefs of student teachers. In regions of cross-cultural diversity the findings may assist in creating understanding and sensitivity of the cultural differences between people, their knowledge, perspectives and practices.